Optimasi Formulasi Kopi Rempah menggunakan Metode Simplex Lattice Design (SLD) sebagai Minuman Fungsional Khas Nusa Tenggara Timur - Aprillia Ni'ma Fajaryanti; Beauty Suestining Diyah Dewanti; Susinggih Wijana (Jurnal Agritechno, 2025)
Functional beverages are increasingly popular due to their health benefits. Spiced coffee has the potential to be developed as a functional drink because of its caffeine and antioxidant content. This study aimed to determine the optimum formulation of Arabica coffee with the addition of spices and to evaluate consumer acceptability. The research design employed the Simplex Lattice Design (SLD) method with coffee concentrations of 94–98% and spice concentrations of 2–6%. The responses observed included antioxidant activity, total phenolic content, and caffeine levels. Data were analyzed using Design Expert 13, while hedonic testing was conducted with Minitab 21 involving 30 panelists. The results indicated that the optimum formulation consisted of 94% coffee and 6% spices, with predicted values of IC50 at 91.428 ppm, total phenolics at 41.105 mg GAE/g, caffeine at 8.569 mg/g, and desirability at 0.865. Sensory evaluation using the 1-sample Wilcoxon test showed that panelists rated the product in the “like” category with a median score of 6, characterized by a dark brown color, dominant spice aroma, and slightly bitter taste.